(untitled) (Training and Practice : Journal of Educational Sciences, 2009)
Until nowadays there was no analysing work made about the methodology, pedagogy and linguistics of Gyula Lux and language teaching in the 1920s. I analysed the books, publications written by Gyula Lux in the field of methodology. To reveal the work of Gyula Lux genuinely, it is crucial to assay the history of education, the cultural policy, education policy of the era in focus, and introduce the theory of curriculum, that meant the basis of my researches. I present the procedure of German language appearing in the Hungarian culture, and the changes in the language-policy, that was a crucial changing point in the Hungarian educational policy, thanks to Kunó Klebelsberg. As most of the work of Gyula Lux consists of language-pedagogy, 1 put emphasis on this area in my work.